2017
DOI: 10.1101/202820
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Extensive non-canonical phosphorylation in human cells revealed using strong-anion exchange-mediated phosphoproteomics

Abstract: Protein phosphorylation is a ubiquitous post-translational modification (PTM) that regulates all aspects of life. To date, investigation of human cell signalling has focussed on canonical phosphorylation of serine (Ser), threonine (Thr) and tyrosine (Tyr) residues. However, mounting evidence suggests that phosphorylation of histidine also plays a central role in regulating cell biology. Phosphoproteomics workflows rely on acidic conditions for phosphopeptide enrichment, which are incompatible with the analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 86 publications
(91 reference statements)
1
8
0
Order By: Relevance
“…Interestingly, Leu residues were globally overrepresented in the sequence motifs surrounding the three phosphoramidate bonds on His, Lys, and Arg but this was not the case when considering the phosphopeptides with phosphorylated Ser, Thr, and Tyr (data not shown). Similar observations were also made by Hardman et al 5 and might suggest selectivity for phosphoramidates bonds or a preferential adsorption to the resins used, but most probably stabilization against hydrolysis by local hydrophobic acids.…”
Section: → Strict Non-acidic Conditions Permit Purification Of Phis Csupporting
confidence: 85%
See 1 more Smart Citation
“…Interestingly, Leu residues were globally overrepresented in the sequence motifs surrounding the three phosphoramidate bonds on His, Lys, and Arg but this was not the case when considering the phosphopeptides with phosphorylated Ser, Thr, and Tyr (data not shown). Similar observations were also made by Hardman et al 5 and might suggest selectivity for phosphoramidates bonds or a preferential adsorption to the resins used, but most probably stabilization against hydrolysis by local hydrophobic acids.…”
Section: → Strict Non-acidic Conditions Permit Purification Of Phis Csupporting
confidence: 85%
“…Phosphoramidate includes the histidine phosphorylation, welldefined in bacteria 3,4 . Regardless of the nature of their chemical linkages, the presence of the phosphate group on all nine amino acids causes an increased mass of 79.97 Da, which can be detected by MS. During phosphopeptide fragmentation, a prominent neutral loss of phosphoric acid (98 Da) is generally observed, and it has been suggested that a triplet neutral loss fingerprint could occur for specific phosphoresidues, but recently this has been called into question [5][6][7] . One of the main reasons why these phosphoramidate bond-containing phosphoamino acids, such as phosphohistidine, have remained unexplored is their instability 8,9 .…”
mentioning
confidence: 99%
“…Recent studies aimed at systematic large-scale detection of six acid-labile protein phosphorylation in human cell extracts have exposed the difficulty of confident localization of phosphate groups on Arg, His, Lys, Asp, Glu, and Cys residues. Although phosphorothiol ester linkage is moderately acid-stable and highly base-stable, protein cysteine phosphorylation was not detected in these studies (Hardman et al 2017). The lack of basic information on the prevalence, properties, and behavior of this modification under analytical circumstances explains this lack of success.…”
Section: Discussionmentioning
confidence: 85%
“…Triplet-like phosphate losses, generated by HCDfragmentation from molecular ions of pCys-peptides, are similar to the neutral-loss triplets (or missing M-116 signal NL-doublets) observed for many phosphohistidine peptides (Oslund et al 2014;Potel et al 2018a). Earlier, Hardman et al had thoroughly evaluated identification of pHis-peptides by the triplet-like loss pattern (Hardman et al 2017) and concluded that this trait was not a general hallmark of histidine phosphorylation.…”
Section: Characteristics Of Hcd-type Fragmentation Of Pcys-peptidesmentioning
confidence: 87%
“…[ 46 ] As another example, a high‐throughput analysis of phospho‐tyrosine has revealed a large proportion of noncanonical P‐sites. [ 51 ] All these data are in accordance with the concept that the structure of the kinase catalytic site is dynamic, and that it adapts to flexible substrates. [ 52 ] To investigate briefly this complexity, we have checked 600 protein substrates of 60 kinases representing the major families retrieved from PhosphoSitePlus and covering more than 10 000 phosphorylated sites as a limited representative panel of the full phospho landscape.…”
Section: Introductionmentioning
confidence: 99%